Credit Quality in Developing Economies : Remittances to the Rescue? - Ebeke, Christian (IMF Working Papers; Working Paper ;, 2014)
This paper analyzes the link between remittances inflows and nonperforming loans (NPLs) in a large sample of developing countries. Theoretical transmission channels include risk coping, exchange rate and growth impacts. Panel data estimates uncover the significant role of remittance inflows in reducing the size of NPLs in recipient economies. Econometric results also indicate a stronger marginal impact of remittances in a context of high macroeconomic instability, suggesting a significant effect of remittances on the likelihood of the private sector's credit default during shocks. These results hold even after factoring in: (i) the endogeneity of remittance inflows and, (ii) the use of an alternative estimator (panel fractional logit) aimed at dealing with bounded dependent variables.